The Seriousness of the Scholars of Hadith in the Second Century of Hijriah in Codifying Hadith - Yusup Muhidin; Engkos Kosasih; Muhammad Al Mighwar (al-Afkar, Journal For Islamic Studies, 2025)
This paper aims to explain the seriousness of hadith scholars in the second century hijriyah in codifying hadith. With the method of library research or library research, namely data collection sourced from books, scientific journals and articles, in which there is information about the efforts of the scholars of hadith in the second century in the codification of hadith. The second-century hadith scholars codified hadith based on their obedience to the orders of Caliph Umar bin Abdul Aziz so that the preservation of hadith could be maintained from time to time. As a result, the writing and collection of hadith done by the scholars gave birth to many works of hadith books that continued to grow and the concerns of the people on the extinction of the hadith were slightly eased.